A DESCRIPTION OF MOTHER'S KNOWLEDGE ABOUT STUNTING IN TODDLERS AGED 25-59 MONTHS AT THE PRATAMA TALIA PANCUR BATU CLINIC, DELI SERDANG REGENCY IN 2022 - Simarmata, Putri Kasih; Veronika, Anita; Br Sitepu, Aprilita; sinabarina, Merlina (Sean Institute, 2022)
Toddler period is the most important period in the life cycle, because at the age of 0 to 5 years, toddlers experience physical, mental and behavioral development. Stunting is a condition in which children experience growth disorders, so that the child's height does not match his age, as a result of chronic nutritional problems, namely lack of nutritional intake for a long time. Based on a preliminary study in May at the Talia Pratama Clinic, it was found that most mothers did not know for sure about stunting in toddlers. Research Objectives: To find out the description of maternal knowledge about stunting in toddlers aged 25-59 months at the Talia Pancur Batu Pratama Clinic, Deli Serdang Regency in 2022. Research Methods: This type of research is descriptive. The sampling technique used was accidental sampling. The location of this research was at the Talia Pratama Clinic in May 2022. With 30 respondents the measuring instrument used was a questionnaire. Research Results: The results showed that of the 30 respondents at the Talia Pratama Clinic, there were 2 respondents in the category who had good knowledge (6.67%), the category with sufficient knowledge is 10 respondents (33.33%), and the category with less knowledge is 18 respondents (60%). Conclusion: Based on the results of the study, it shows that most of the respondents have less knowledge (60%). Health workers are expected to increase counseling in polyclinics so that mothers' knowledge about stunting in toddlers increases and invites mothers to seek information from health workers.